The Effect of Work Life Balance and Job Training on Employee Performance: Job Satisfaction as Mediation - Jamilah, Jamilah; Kambara, Roni; Ana Susi Mulyani (Asean International Journal of Business, 2024)
Purpose - The purpose of this research is to determine the effect of work life balance and job training on employee performance with job satisfaction as mediation in PT. BPR Berkah. Methodology/approach - This research uses a quantitative methods with census sampling techniques. The sample in this study are all employees who work in PT. BPR Berkah. Data collection is carried out through online and offline distribution of questionnaires.The data analysis method uses Structur Equation Modelling (SEM), 48 samples were taken. The analysis technique in this study is Partial Least Square (PLS) with the help of SmartPLS 4.0 software. Findings – Job training has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, work life balance has a positive but not significant effect on job satisfaction, job training has a positive and significant effect on job satisfaction, and job satisfaction can mediate relationship between work life balance and employee performance. Novelty/value – Job Training and Job Satisfaction are important in improving employee performance.